Natural science from the worldview of the Qur'an: an introduction - volume 3 - Zubir, Nazira; Awang, Zolkofli; Mohd. Dani, Siti Mardziah; Hassan, Nur Jannah; Sabri, Sabrina; Mohd. Yusof, Mohd Isa; Husin, Abu Hassan; Hassan, Mohd Kamal (Institut Terjemahan & Buku Malaysia (ITBM), 2018)
Volume three, the last of a three-volume work on natural science for secondary school students, consists of three chapters. CHAPTER 1 carries the theme "management of the environment, balance, sustainability and the continuity of life". It starts with an elaboration of biodiversity followed by the nature of interdependence among living things and the environment. What naturally follow are matters of concern in regards to the preservation and conversation of the environment, which are of great importance and pivotal concern in the qur'anic worldview. The world around us is visualised through our senses. Since our daily living depends on them, the matter of nutrition and production of food is dealt with. The physiological functions of living things on which life depends so much, such as circulation, reproduction, coordination and heredity are elaborated upon.